Light Induction of Phosphoenolpyruvate Carboxylase in Etiolated Maize Leaf Tissue - Hayakawa, Shinobu (1981)
An antibody for phosphoenolpyruvate carboxylase was used to isolate and to quantitate the enzyme from greening maize (cv. KOU 6) leaves. The increase in enzyme activity during greening was due to de novo synthesis, which was paralleled by increases in enzyme protein and incorporation of leucine. The light-induced activity was due to one specific isoenzyme. The action spectrum for enzyme synthesis had red and blue peaks.